Analysis of I-V characteristics of Pd/ZnO thin Film/n-Si schottky diodes with series resistance - Somvanshi D.; Jit S. (My University, 2025)
The measured current-voltage characteristics have been analyzed by using conventional thermionic emission model, Cheung's method and Norde's technique to estimate the barrier height, ideality factor and series resistance of the vertical Pd/n-ZnO thin film Schottky contacts grown on n-Si substrates by thermal evaporation method. While the conventional analysis gives barrier height ~0.67 eV, ideality factor ~2.36 and series resistance ~5333Ω, the Cheung's method has resulted in nearly same barrier height ~0.67 eV but a much larger value of ideality factor ~5.29 and a relatively smaller value of series resistance ~4734Ω. The Norde's method results in nearly a same value of barrier height ~0.67 eV but a much larger value of barrier height ~30.983×103 Ω than the other two approaches. The study shows that Cheung's method could be the best and most practical for estimating the diode parameters including the effect of series resistance of the Pd/n-ZnO thin film/n-Si Schottky diode structures under consideration. © 2014 American Scientific Publishers.